2013
DOI: 10.1590/s1516-14392013005000047
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing effect on fatigue crack propagation at the heat-affected zone of AISI 4140 steel shielded metal arc weldings

Abstract: The fractography and mechanical behaviour of fatigue crack propagation in the heat-affected zone (HAZ) of AISI 4140 steel welded using the shielded metal arc process was analysed. Different austenitic grain size was obtained by normalizing performed at 1200 °C for 5 and 10 hours after welding. Three point bending fatigue tests on pre-cracked specimens along the HAZ revealed that coarse grains promoted an increase in fatigue crack growth rate, hence causing a reduction in both fracture toughness and critical cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Figure 5 b,c also represent the typical transgranular crack morphology with the river patterns which indicate the direction of localized crack propagation [ 45 , 55 , 56 ]. It was observed that the presence of this transgranular cleavage fracture mechanism in steel is related to iron carbides (cementite) [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 b,c also represent the typical transgranular crack morphology with the river patterns which indicate the direction of localized crack propagation [ 45 , 55 , 56 ]. It was observed that the presence of this transgranular cleavage fracture mechanism in steel is related to iron carbides (cementite) [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%